Assessment of motion gating strategies for mouse magnetic resonance at high magnetic fields. - Cassidy, P; Schneider, J; Grieve, S; Lygate, C; Neubauer, S; Clarke, K (2004)
PURPOSE: To assess the performance of motion gating strategies for mouse cardiac magnetic resonance (MR) at high magnetic fields by quantifying the levels of motion artifact observed in images and spectra in vivo. MATERIALS AND METHODS: MR imaging (MRI) of the heart, diaphragm, and liver; MR angiography of the aortic arch; and slice-selective 1H-spectroscopy of the heart were performed on anesthetized C57Bl/6 mice at 11.75 T. Gating signals were derived using a custom-built physiological motion gating device, and the gating strategies considered were no gating, cardiac gating, conventional gating (i.e., blanking during respiration), automatic gating, and user-defined gating. Both automatic and user-defined modes used cardiac and respiratory gating with steady-state maintenance during respiration. Gating performance was assessed by quantifying the levels of motion artifact observed in images and the degree of amplitude and phase stability in spectra. RESULTS: User-defined gating with steady-state maintenance during respiration gave the best performance for mouse cardiac imaging, angiography, and spectroscopy, with a threefold increase in signal intensity and a sixfold reduction in noise intensity compared to cardiac gating only. CONCLUSION: Physiological gating with steady-state maintenance during respiration is essential for mouse cardiac MR at high magnetic fields.